PENGARUH MOTIVASI DAN PELIMPAHAN WEWENANG SEBAGAI VARIABEL MODERATING TERHADAP HUBUNGAN ANTARA PARTISIPASI PENYUSUNAN ANGGARAN DAN KINERJA MANAJERIAL - Adiputra, I Made Pradana; Ghozali, Imam (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2002)
Most of accounting studies had examined the relationship between budget participation and managerial performance. However, the result of previous studies showed that their relationship were not consistent. To reconcile these conflicting results, it needs to investigate the hypothesized relationship using a contingency approach.This study empirically examined the influence of motivation and delegation of authority as moderating variables on the relationship between budget participation and magerial performance. Mailed quitionnaires were distributed to 1120 managers or head of division/chief officer was high qualified hotels in Bali. The responses from 154 (13, 75 %) managers or head divisio11/chief officer analyzed by using regression analysis with residuai approach (bivariate test).The results of study showed that budget participation and managerial performance had positive and significant relationship. The results also showed that a high degree of fit between budget participation and contingent variable motivation influenced the increasing of manag1Jrial performance. Otherwise, result of study about the influence of a high degreP, of flt between budget participation and contmgent variable delegation of authority showed positive and significant result on the increasing of managerial performance.